PREGNANCY EXPERIENCE WITH EARLY MARRIAGE - Pertiwi, Nur Fitri Ayu; Laela Abida, Liza; Nurlaili, Helmi (Jurnal Fisioterapi dan Kesehatan Indonesia, 2025)
Early marriage in Indonesia has a negative impact on women's physical, psychological, and social health. This study explores the experience of first pregnancy in women who married early in Rancabungur District, Bogor Regency. The method used is qualitative research with in-depth interviews. The sample in this study was 5 main informants of teenagers who experienced early marriage and 4 supporting informants. The results of the study are expected to help formulate policies to prevent early marriage. Teenage pregnancy due to early marriage is often accompanied by unpreparedness and dependence on parents. Appropriate education and assistance are needed to support the health of young mothers. Keywords: early marriage, pregnancy, experience